Некоторые вопросы методологии в английской исторической диалектологии - Армалите, О. (Kalbotyra, 1975)
The present article is an attempt to survey different methodological approaches to the main problem of English historical dialectology, the problem of dialectal differentiation of early periods of English. Structural approach is viewed as the most acceptable. It treats dialects as diverging systems within a framework of similarities of one language. On the phonological level dialectal differences form a distinct system. The dialectal peculiarities of old written monuments, belonging to a particular territory, can be viewed as a system, formed in the historical development of the language. Phonological dialectal differences can be general and isolated. General (paradigmatic) differences include differences in the inventory of the phonemes and differences in the distinctive features. Isolated dialectal differences are differences in the phonetic realization of the phonemes as well as differences in the distributional properties of the phonemes (syntagmatic differences). Phonological dialectal differences manifest themselves more obviously on the phonetic level and in the distributional properties of the phonemes.